Additional Malignant Breast Lesions Detected on Second-Look US After Breast MRI vs. Additional Malignant Lesions Detected on Initial US in Breast Cancer Patients: Comparison of US Characteristics - Park, V. Y.; Kim, M. J.; Moon, H. J.; Kim, E. K. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: The purpose of our study was to review and compare the US findings of synchronous malignant breast lesions other than the index cancer additionally detected on second-look US with those detected on initial US, and therefore to determine differing characteristics that may aid in diagnosis and essentially improve the performance of the initial US examination.Materials and Methods: A retrospective review of 39 mammographically occult synchronous malignant lesions other than the index cancer from 38 patients was performed (21 lesions: detected on second-look US, 18 lesions: detected on initial US). All patients underwent initial mammography, bilateral whole breast US (BWBU) and breast MRI, and all lesions were confirmed pathologically by biopsy or preoperative localization.Results: Additional malignant breast lesions detected on both initial US and second-look US tended to be subtle and often did not show classic malignant findings. Second-look US lesions (median, 7.0 mm; range, 3 – 22 mm) tended to be smaller than initial US lesions (median, 9.0 mm; range 3 – 45 mm), although the difference was not statistically significant (p = 0.134). Second-look US lesions also showed no posterior acoustic features (p = 0.037) and a significantly higher proportion of lesions with circumscribed or indistinct margins compared to initial US lesions (p = 0.042). Second-look US lesions were significantly subareolar or relatively far (> 5 cm) from the nipple than initial US lesions (p = 0.048).Conclusion: Second-look US lesions showed more subtle findings of posterior acoustic features and margins, and tended to be subareolar or relatively far from the nipple compared to initial US lesions. However, both groups showed subtle US findings and there was no significant difference in other features.
Keywords: breast; ultrasound; second-look